Implementation of the golden age islamic boarding school program in improving the quality of life of elderly students at the Daarut Tauhiid Islamic Boarding School - Habibah, Nafahatul; Alawiyah, Mudrikah Romdona; Faujiah, Risnawati Sarifah; Muhyiddin, Afif Muhammad; Rosadi, Umar (Educenter : Jurnal Ilmiah Pendidikan, 2024)
The Golden Age Program is a program that aims to foster Muslims and Muslim women at the golden age to have a straight creed, correct worship and noble character. In accordance with its title, "IMPLEMENTATION", this study aims to determine the planning of the Golden Age Program, obtain data on the implementation of the Golden Age Program program, and find out the evaluation process of the Golden Age Program at Daaarut Tauhid Islamic Boarding School. This research methodology uses a qualitative approach with data collection techniques in the form of in-depth interviews, participatory observation, and document analysis. The results of this study explain that the Golden Age Program planning is packaged in the form of training with an Andragogy approach. Consists of setting goals and objectives, program background, curriculum development, education calendar preparation, resource procurement. Then the implementation of the Service Period Program there are activities and activities that will be carried out by elderly students such as registration, testing, orientation period, teaching and learning activities, monitoring and mentoring, evaluation and graduation. Furthermore, the evaluation of the Elderly Period Program is carried out by means of analysis and assessment, collection of feedback, preparation of reports, recommendations and planning for the future.